The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023 IEEE/ACM 45th International Conference on Software Engineering: Software Engineering Education and Training (ICSE-SEET) 2023
DOI: 10.1109/icse-seet58685.2023.00019
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Girls in Computer Science: Do Single-Gender Interdisciplinary Classes Help?

Abstract: Computing-driven innovation cannot reach its full potential if only a fraction of the population is involved. Without girls and their non-stereotypical contribution, the innovation potential is severely limited. In computer science (CS) and software engineering (SE), the gender gap persists without any positive trend. Many girls find it challenging to identify with the subject of CS. However, we can capitalize on their interests and create environments for girls through interdisciplinary subcultures to spark a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Gender-sensitive Pedagogy or Gender-sensitive Teaching [10,[117][118][119][120][121][122][123]126,129,130,132,139,140,159,162,176,187,191,192,195] Gender-sensitive Research [10,[117][118][119][120][121][122][123][124][125][126][127]129,139,140,158,159,163,176,177,187,191,192,195,199] Goal 5 or SDG 5 [3,27,32,44,…”
Section: Topics Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender-sensitive Pedagogy or Gender-sensitive Teaching [10,[117][118][119][120][121][122][123]126,129,130,132,139,140,159,162,176,187,191,192,195] Gender-sensitive Research [10,[117][118][119][120][121][122][123][124][125][126][127]129,139,140,158,159,163,176,177,187,191,192,195,199] Goal 5 or SDG 5 [3,27,32,44,…”
Section: Topics Referencesmentioning
confidence: 99%
“…Interestingly, it was found that girls in single-gender classes (SGCs) exhibited a noticeably greater openness to computerrelated subjects. Moreover, the intervention elicited more positive responses from girls in SGCs than those in mixed-gender classes (MGCs) [122].…”
mentioning
confidence: 99%